Empirically based composite fracture prediction model from the Global Longitudinal Study of Osteoporosis in Postmenopausal Women (GLOW). - FitzGerald, G; Compston, J; Chapurlat, R; Pfeilschifter, J; Cooper, C; Hosmer, D; Adachi, J; Anderson, F; Díez-Pérez, A; Greenspan, S; Netelenbos, J; Nieves, J; et al. (Endocrine Society, 2014)
CONTEXT: Several fracture prediction models that combine fractures at different sites into a composite outcome are in current use. However, to the extent individual fracture sites have differing risk factor profiles, model discrimination is impaired. OBJECTIVE: The objective of the study was to improve model discrimination by developing a 5-year composite fracture prediction model for fracture sites that display similar risk profiles. DESIGN: This was a prospective, observational cohort study. SETTING: The study was conducted at primary care practices in 10 countries. PATIENTS: Women aged 55 years or older participated in the study. INTERVENTION: Self-administered questionnaires collected data on patient characteristics, fracture risk factors, and previous fractures. MAIN OUTCOME MEASURE: The main outcome is time to first clinical fracture of hip, pelvis, upper leg, clavicle, or spine, each of which exhibits a strong association with advanced age. RESULTS: Of four composite fracture models considered, model discrimination (c index) is highest for an age-related fracture model (c index of 0.75, 47 066 women), and lowest for Fracture Risk Assessment Tool (FRAX) major fracture and a 10-site model (c indices of 0.67 and 0.65). The unadjusted increase in fracture risk for an additional 10 years of age ranges from 80% to 180% for the individual bones in the age-associated model. Five other fracture sites not considered for the age-associated model (upper arm/shoulder, rib, wrist, lower leg, and ankle) have age associations for an additional 10 years of age from a 10% decrease to a 60% increase. CONCLUSIONS: After examining results for 10 different bone fracture sites, advanced age appeared the single best possibility for uniting several different sites, resulting in an empirically based composite fracture risk model.